Emerging aluminium nitride nanoparticles: chemical synthesis and exploration of their biocompatibility and anticancer activity against cervical cancer cells - Manjot Kaur (Nanomedicine Journal, 2020)
Objective(s): Aluminium nitride (AlN) could be used in implantable biomedical sensor devices, for which cytotoxicity analysis is of utmost importance. Materials and Methods: AlN nanoparticles were synthesized using a simple and effective solvothermal method. The X-ray diffraction results revealed the cubic phase of AlN, and the field emission scanning electron microscopy analysis demonstrated the structural morphology of the synthesized materials. In addition, the cytotoxicity of the AlN nanoparticles was assessed against healthy (HEK-293, HUVEC, and MCF10A) and cancerous cell line (HeLa). The intensity of the reactive oxygen species was also measured to determine the induced oxidative stress in the treated cells. Results: The cytotoxicity analysis indicated that the AlN nanoparticles were nontoxic against the cancerous and normal cell lines. No significant changes were observed between the low doses of the AlN nanoparticles in the treated and control cells. However, morphological changes were detected by a phase contrast microscope, while insignificant changes were observed similar to the control cells. Conclusion: The findings of this study could lay the groundwork for the development of AlN nanoparticles for further biomedical applications.